Missing elements in US financial reform: A Kübler-Ross interpretation of the inadequacy of the Dodd-Frank Act - Kane, Edward J. (Journal of Banking & Finance, 2012)
The success of any treatment plan depends on how completely the problems it targets have been diagnosed. The precrisis bubble in securitization can be traced to incentive conflict that allows national safety nets to subsidize leveraged risk-taking. Safety-net subsidies encouraged regulation-induced innovations that enabled firms to take hard-to-monitor risks and to make themselves politically, administratively, and economically difficult for government officials to fail and unwind. This paper summarizes the incentive conflicts that led creditors and internal and external supervisors to short-cut and outsource due diligence. The Dodd-Frank strategy of reform does not adequately acknowledge or address these conflicts. The key step needed is to develop an effective statistical metric for measuring the ex ante value of safety-net support in the aggregate and at individual institutions. To accomplish this, government and industry need to rethink the informational obligations that insured financial institutions and their regulators owe to taxpayers as de facto investors and to change the way that information on industry balance sheets and risk exposures is reported, verified, and used. Without reforms in the practical duties imposed on industry and governmental officials and in the way these duties are enforced, financial safety nets will continue to expand and their expansion will undermine financial stability by generating large rewards for creative and aggressive risk-takers that are smart enough to cash in their share of safety-net benefits before they evaporate.